PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DISERTAI TREE CHART TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 2 LUBUK SIKAPING KABUPATEN PASAMAN - Febriani, Meriza; Risdawati, Renny; Suheni, Suheni (STKIP PGRI Sumbar, 2013)
ABSTARCTThis study aims to determine the learning outcomes of students with the application of cooperative learning model jigsaw with tree chart in biology learning in class VII SMPN 2 Lubuk Sikaping Pasaman. Types of research used in this study is a design experiment with a posttest only control group design. Population in this study were all students of class VII SMPN 2 Lubuk Sikaping Pasaman in the school year 2012/2013. Of this study it can be concluded that the jigsaw cooperative learning model with tree chart positif effect on learning outcomes biology class VII SMPN 2 Lubuk Sikaping Kabupaten Pasaman.